Interaction of two edge dislocations in free-space propagation - 何德 高曾辉 闫红卫 吕百达 (Chinese physics B, 2011)
This paper studies in detail the interaction of two edge dislocations nested in a Gaussian beam propagating in free space. It shows that in free-space propagation the edge dislocations are unstable and vanish, and two noncanonical vortices with opposite topological charge take place when off-axis distances cl and c2 of two edge dislocations are nonzero, and the condition k2w08＋ 32c1c2（w02- 2C1C2）Z2 〉 0 is fulfilled （k-wave number, w0-waist width）. A noncanonical vortex appears when one off-axis distance is zero. However, one edge dislocation is stable when two edge dislocations are perpendicular and one off-axis distance is zero. Two perpendicular edge dislocations both with zero off-axis distance are also stable. The analytical results are illustrated by numerical examples.